Imperfectly credible disinflation under endogenous time-dependent pricing - Marco Bonomo; Carlos Carvalho (Federal Reserve Bank of New York, 2008)
The real effects of an imperfectly credible disinflation depend critically on the extent of price rigidity. In this paper, we examine how credibility affects the outcome of a disinflation in a model with endogenous time-dependent pricing rules. Both the endogenous initial degree of price rigidity and changes in the duration of price spells during disinflation play an important role in explaining the effects of imperfect credibility. We initially consider the costs of disinflation when the degree of credibility is fixed, and then allow agents to use Bayes' rule to update beliefs about the 'type' of monetary authority that they face. In both cases, the interaction between the endogeneity of time-dependent rules and imperfect credibility increases the output costs of disinflation. The pattern of the output response is more realistic in the case with learning.
Keywords: E31; E52; 330; Disinflation; optimal price setting; endogenous time-dependent pricing; Inflationsbekämpfung; Preisrigidität; Theorie